Numerical simulation of plain concrete specimens with micromechanical model and simple lattice model - Teng, Susanto (2017)
In this paper, a recently proposed micromechanical model for concrete is combined with a simple lattice model to simulate the behaviours of plain concrete specimens under tension, compression and three-point bending. The Mori–Tanaka method based micromechanical model for concrete considers the microcracks around the mortar–coarse aggregate interface and the aligned coalesced cracks in the concrete. It explicitly correlates the mechanical properties of concrete with the properties of its constituents such as mortar and coarse aggregates. The adopted simple lattice model, in which the axial interaction between neighbouring points is considered as a truss, does not need to generate grain structure and is thus easy to implement. Hence, this combination can be used to investigate the influences of the concrete constituents' properties on the behaviours of the concrete specimens in a simple way. The predicted deformation responses and crack patterns from the computational model are generally in agreement with the experimental observations.